Pengalaman Pembelajaran Informal dalam kalangan Pengusaha Bengkel Automotif di Kota Tinggi, Johor: [Informal Learning Experiences Among Automotive Workshop Entrepreneur in Kota Tinggi, Johor] (Sains Humanika, 2021)
This research purpose is to examine the informal learning among automotive workshop entrepreneurs. Three research objectives such as informal learning factors, informal learning strategies and informal learning effects are also identified. This study used a case study by using a qualitative method. Semi-structured interviews have been used for data collection. By using purposive sampling, five automotive workshop entrepreneurs in Kota Tinggi were selected as respondents. The findings show that individual needs, environment, interests, motivations and job requirements have been factors that help automotive workshop entrepreneurs involved in informal learning. In addition, reading materials, electronic media, observation, consulting with experts and try and error are informal learning strategies that have been used. Moreover, the effects of informal learning can be seen as the enhancement of knowledge and skills. Meanwhile, there has been a positive change in the attitude of automotive workshop entrepreneurs. This study also provided suggestions for improvement to future researchers.
Keywords: Adult learning, informal learning, case study, automotive workshop, self-directed learning